Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. Using Altman Model in Predicting Financial Default in Saudi Banking Sector: Comparative Study Pre- and Post Corona PandemicDr. May Abdulaziz Alamoudi, Ms. Muruj Alharbi2. The effect of administrative control on the effectiveness of decisions in Omani government institutionsMr. Hatem bin Abdullah bin Muhammad Al-Shezawi3. Career succession planning and its role in improving professional competencies of human resources in educational institutionsDr. Huda Salem Moawad4. Measuring the impact and the extent of satisfaction of owners of small and medium enterprises benefiting from the support services provided by the Jordanian Small and Medium Enterprises Corporation during the period (2016-2022)Dr. Osama Suliman Alsalaheen, Dr. Ameen Sulieeman Alzubaidi, Dr. Ameen Osama Shammout5. Job Motivation and Its Impact on Supporting Security Creativity and Innovation: An Applied Study on the General Command of Sharjah PoliceMrs. Amna Ali Hassan Abdullah6. The Role of Lean Management in Enhancing Job Performance: An Applied Study on the Ministry of Health in Saudi ArabiaMs. Muneera Musallat Fahad Al-Otaibi7. Digital Transformation in Public Organizations: An Applied Study on the Ministry of Health in the Kingdom of Saudi ArabiaDr. Ahmad Adil Saqqat8. The Effect of Perceived Audit Quality on the Relationship between Other Comprehensive Income and Earnings Management for Listed Companies in Saudi Stock ExchangeMs. Ibtihal Abdullah Alkhorayef, Dr. Mohamed Khames Zaytoun
Keywords: Journal of Economic, Administrative and Legal Sciences